Artificial Intelligence in Prenatal Ultrasound: Clinical Application and Prospect - Wenjia Guo, MM, Shengli Li, MM, Xing Yu, MD, Huaxuan Wen, BM, Ying Yuan, MM, Xia Yang, MM (Advanced Ultrasound in Diagnosis and Therapy, 2023)
Since the 1990s, researchers have been seeking approaches for applying artificial intelligence (AI) to prenatal ultrasound. With the breakthrough of cloud computing technology and the development of deep learning technology, AI in prenatal ultrasound has already entered the clinical application stage in recent years. How does AI combine with clinical prenatal ultrasound? Is the clinical application of AI in prenatal ultrasound effective? What can we expect from AI in prenatal ultrasound? This review introduces the latest developments in this field and explores the challenges and opportunities brought by AI to prenatal ultrasound.